Espacialidad y ordenamiento territorial quillacinga: caminos y asentamientos prehispánicos en el suroccidente colombiano, el caso de Genoy - Fierro Leyton, Tiepolo David (2024)
The high archaeological potential of southwestern Colombia is reflected in movable vestiges of cultural heritage such as ceramics, metallurgy and rock art, but also in elements of ancestral road infrastructure, currently used by the descendants of those peoples who inhabited this region before the arrival of the Spanish. This work seeks to make visible the spatial relationship between settlements and pre-Hispanic roads, inscribed within an organization of the landscape and territory by human groups that the Spanish called quillacingas. To do this, we have focused on studying the area corresponding to the current township of Genoy, located northwest of the city of Pasto, in the department of Nariño (Colombia). In this territory today, indigenous authority still persists, manifested in the legal entity of the Quillacinga Indigenous Council of Genoy, who has managed to preserve and recover much of the cultural heritage and material culture of their ancestors. Based on the experiences of researchers such as Robert Drennan and Carl Langebaek in other areas of Colombia, a regional recognition methodology was developed that allowed the identification of settlement patterns and a spatial link between domestic contexts, roads and geoforms in this cultural landscape constructed by the ancestors of the quillacinga people. The information collected allowed us to establish the anthropic modifications of the pre-Hispanic landscape, the transformations that occurred during the Colonial period, and the importance of compressed verticality in the socioeconomic relations and worldview of the original inhabitants of this area of the Northern Andes.